In vivo evaluation of mineral bioavailability in groundnut haulm based complete diets supplemented with organic and inorganic mineral sources in goats - RANI, K SUDHA; RAMANA, J V; DEVASENA, B; GOWDA, N K S; REDDY, P SUDHAKARA (The Indian Journal of Animal Sciences, 2015)
A study was carried out to evaluate in vivo mineral bio-availability in groundnut haulm based complete diets supplemented with organic and inorganic mineral sources in goats. A basal complete diet was prepared with GNH and concentrate mixture (8% maize, 10% soybean meal, 21.5% de-oiled rice bran and 0.5% salt) in 60: 40 ratio. The basal diet was treated as control (T1) and 3 more diets were prepared by supplementing basal diet with commercial mineral mixture at 1.5% (T2), inorganic mineral supplements at 26.4g (8.3 g ZnSO4, 4.0 g CuSO4 and 14.0 g MnSO4) (T3) and organic mineral supplements @ 72g (12g Zn-P,10 g Cu-P and 50g Mn-P) (T4). The CP, CF, EE, TA, AIA and NFE contents of the basal diet were 15.8, 20.0, 1.4, 17.8, 9.7 and 45.0% respectively. In vivo metabolic studies were carried out on 4 complete diets T1, T2, T3 and T4. The DMI was 2.7 kg/% body weight which is in accordance with ICAR (1998) recommendation. The DCP intake was 115.7, 121.2, 117 and 117 g/animal/day in T1, T2, T3 and T4 respectively. There was no significant difference between treatments with regard to DMI or DCP intake. Significant differences were also not observed between treatments with regard to total nitrogen excretion (g/day), N retention (g/day) and N retention expressed as % of intake. The N-retention expressed as % of intake in T1, T2, T3 and T4 were 57.1, 58.1, 52.0 and 54.1% respectively. The mineral supplementation did not influence the nitrogen retention in all the treatments. Positive nitrogen balances were observed in all the treatments showing that there was no negative effect of mineral supplementation on N- balance. The copper retention expressed as % of Cu intake in T1, T2, T3 and T4 were 65.1, 64.8, 70.8 and 75.0% respectively, suggesting that significant differences were observed between the treatments with regard to Cu intake (g/d) and copper retention (g/day). The zinc retention (g/day) and zinc retention expressed as per cent of intake showed significant differences between the treatments. Mn retention expressed as per cent of intake was 18.0, 38.2, 32.3 and 33.7% respectively in T1, T2, T3 and T4 treatments. Significant differences were observed between the treatments with regard to Mn intake (g/day), Mn retention and Mn retention expressed as % of intake. The plasma Cu, Mn and Zn concentrations in all the animals increased at the end of the metabolic study, as compared to the values at the start of the experiment. It can be concluded that the organic mineral supplements were better bio-available than the inorganic mineral supplements.